The methods of confronting the pressures and their relationship with the grief among the sons of martyrs of the war on Gaza - Palestine - Alyan, Mohamed Mohamed; Al Kahlout, Emad Hanoun (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to identify the methods of coping with the most common pressures and to detect the level of grief and differences in each of the methods of coping with stress and sadness depending on the gender difference of the sample, and to verify the difference in methods of coping with pressure according to the level of grief and the impact of interaction between sex and grief on methods to confront the pressure of the sample Gaza Governorates. The study sample consisted of (260) children of martyrs registered in preparatory schools in the Gaza Strip in Palestine, 122 of whom were males and 138 of them were between the ages of 12 and 16 years. (Carver et al., 1989), and the Gauges of Grief (Faschingbauer, 1987). The results of the study showed that the level of grief was 72.7% in the sample. The religious adjustment method came first with 86.7% of the sample, followed by planning with a relative weight of 76.8% and a positive re-evaluation of 72.6%. In contrast, the method of ridicule comes at the end of the list of methods used by the respondents in facing the stressful events with a relative weight of 48.4%, followed by the behavioral withdrawal with a relative weight of 54.3% and the denial of a relative weight of 56.5%. And preoccupation with thinking in favor of the high of grief. The results did not find a statistically significant effect of the interaction between sex and grief on the methods of coping with pressure in the sample.
Keywords: methods; confrontation; pressure; grief; children of war martyrs; Palestine